Confocal μ-XANES as a tool to analyze Fe oxidation state in heterogeneous samples: the case of melt inclusions in olivine from the Hekla volcano - Botcharnikov, Roman; Wilke, Max; Garrevoet, Jan; Portnyagin, Maxim; Klimm, Kevin; Buhre, Stephan; Krasheninnikov, Stepan; Almeev, Renat; Moune, Severine; Falkenberg, Gerald (Göttingen : Copernicus Publications, 2024)
Here we present a confocal Fe K-edge μ-XANES method (where XANES stands for X-ray absorption near-edge spectroscopy) for the analysis of Fe oxidation state in heterogeneous and one-side-polished samples. The new technique allows for an analysis of small volumes with high spatial 3D resolution of <100 μm3. The probed volume is restricted to that just beneath the surface of the exposed object. This protocol avoids contamination of the signal by the host material and minimizes self-absorption effects. This technique has been tested on a set of experimental glasses with a wide range of Fe3+ / ςFe ratios. The method was applied to the analysis of natural melt inclusions trapped in forsteritic to fayalitic olivine crystals of the Hekla volcano, Iceland. Our measurements reveal changes in Fe3+ / ςFe from 0.17 in basaltic up to 0.45 in dacitic melts, whereas the magnetite-ilmenite equilibrium shows redox conditions with Fe3+ / ςFe ≤0.20 (close to FMQ, fayalite-magnetite-quartz redox equilibrium) along the entire range of Hekla melt compositions. This discrepancy indicates that the oxidized nature of glasses in the melt inclusions could be related to the post-entrapment process of diffusive hydrogen loss from inclusions and associated oxidation of Fe in the melt. The Fe3+ / ςFe ratio in silicic melts is particularly susceptible to this process due to their low FeO content, and it should be critically evaluated before petrological interpretation.